Inositol 1, 4, 5‐trisphosphate receptor regulates replication, differentiation, infectivity and virulence of the parasitic protist Trypanosoma cruzi. Issue 6 (4th February 2013) - Hashimoto, Muneaki; Enomoto, Masahiro; Morales, Jorge; Kurebayashi, Nagomi; Sakurai, Takashi; Hashimoto, Tetsuo; Nara, Takeshi; Mikoshiba, Katsuhiko
Summary In animals, inositol 1, 4, 5‐trisphosphate receptors (IP3Rs) are ion channels that play a pivotal role in many biological processes by mediating Ca2+ release from the endoplasmic reticulum. Here, we report the identification and characterization of a novel IP3R in the parasitic protist, Trypanosoma cruzi, the pathogen responsible for Chagas disease. DT40 cells lacking endogenous IP3R genes expressing T. cruzi IP3R (TcIP3R) exhibited IP3‐mediated Ca2+ release from the ER, and demonstrated receptor binding to IP3. TcIP3R was expressed throughout the parasite life cycle but the expression level was much lower in bloodstream trypomastigotes than in intracellular amastigotes or epimastigotes. Disruption of two of the three TcIP3R gene loci led to the death of the parasite, suggesting that IP3R is essential for T. cruzi. Parasites expressing reduced or increased levels of TcIP3R displayed defects in growth, transformation and infectivity, indicating that TcIP3R is an important regulator of the parasite's life cycle. Furthermore, mice infected with T. cruzi expressing reduced levels of TcIP3R exhibited a reduction of disease symptoms, indicating that TcIP3R is an important virulence factor. Combined with the fact that the primary structure of TcIP3R has low similarity to that of mammalian IP3Rs, TcIP3R is a promising drug target for Chagas disease.